Smart Pallet Tilt Monitoring System With Immediate Notification - Anuar, Nur Amyza; Jalaludin, Nor Anija; Amirul Syafiq Sadun, (Progress in Engineering Application and Technology, 2024)
This project introduces a groundbreaking prototype of a Smart Pallet Tilt Monitoring System with Immediate Notification. The system leverages the MPU6050 sensor to create a robust pallet management solution. The primary objectives encompass the design of a gyroscope-based monitoring system capable of detecting pallet tilt or inclination, integration with the Blynk platform for real-time monitoring, and implementation of an ESP8266-based notification system to alert responsible personnel when dangerous tilt angles are exceeded. Through this integration, the system significantly enhances workplace safety by promptly detecting pallet tilts, facilitating real-time monitoring, and ensuring timely notifications to prevent accidents or damages. Experimental results demonstrate the system's precision, with tilt angle readings exhibiting a low average percent error of around 2.5 percent. This comprehensive approach not only enhances operational efficiency but also fosters a safer and more proactive approach to pallet management, addressing crucial aspects of inventory control and workplace safety in the industry.